(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The main lexical translation transformations used during translating English informative texts into Ukrainian are revealed and described. The author argues that a way of translating lexical elements depends on peculiarities of lexical-semantic systems of original and target languages, functional and stylistic features of words, national-cultural factors.